2013
DOI: 10.1016/j.exger.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet habits in older individuals: Associations with cognitive functioning and brain volumes

Abstract: To examine the association between dietary habits, cognitive functioning and brain volumes in older individuals, data from 194 cognitively healthy individuals who participated in the Prospective Investigation of the Vasculature in Uppsala Seniors cohort were used. At age 70, participants kept diaries of their food intake for 1week. These records were used to calculate a Mediterranean diet (MeDi) score (comprising dietary habits traditionally found in Mediterranean countries, e.g. high intake of fruits and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 33 publications
3
108
2
1
Order By: Relevance
“…Among these studies, highly significant inverse associations were obtained in cross-sectional analyses in Chicago [26] and in Puerto Rican Americans in Boston [27], as well as in the longitudinal Nurses' Health Study [28]. Other studies found borderline significant inverse associations overall in the USA [29] and in Sweden [30], or in subgroups of the studied populations in France [31] and Greece [32]. A weak and nonsignificant inverse association emerged when we evaluated MD adherence in relation to a single MMSE performance in our cohort of elderly men and women [33].…”
Section: Discussionmentioning
confidence: 88%
“…Among these studies, highly significant inverse associations were obtained in cross-sectional analyses in Chicago [26] and in Puerto Rican Americans in Boston [27], as well as in the longitudinal Nurses' Health Study [28]. Other studies found borderline significant inverse associations overall in the USA [29] and in Sweden [30], or in subgroups of the studied populations in France [31] and Greece [32]. A weak and nonsignificant inverse association emerged when we evaluated MD adherence in relation to a single MMSE performance in our cohort of elderly men and women [33].…”
Section: Discussionmentioning
confidence: 88%
“…There was suggestive evidence that a higher consumption of milk and dairy was associated with a lower MMSE score, but this was found only in men and not in women (32). Furthermore, Titova et al (49) showed that meat consumption was associated with a worse cognitive performance. In the study by Cherbuin and Anstey (35), consumption of fish and vegetables was associated with a greater risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 95%
“…Redefining the strategy by which current and future NIH research budget is allocated is of particular relevance, especially considering the major role played by lifestyle factors, such as nutrition, physical activity, and level of cognitive training in the determination of AD risk [27][28][29][30][35][36][37] as well as the proven efficacy of intervention strategies aimed at preventing dementiarelated symptoms [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies aiming to identify the genetic susceptibility to AD and the interaction between specific genetic variations and nutrient intake might be invaluable in designing patient-tailored therapies and preventive approaches based on patient genetic makeups. Novel and more powerful in vivo imaging readouts, such as ultra-high-field magnetic resonance imaging (MRI) and positron emission tomography, are currently available to diagnose AD [86,87] and assess the effects of specific nutritional interventions [88][89][90]. Additionally, novel human connectomics (the production and study of connectomes) provides a three-dimensional reconstruction of neuronal networks within the human brain.…”
Section: The Population and Individual Levels: Epidemiological Studiementioning
confidence: 99%